2023
DOI: 10.1111/ele.14218
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic efficiency reshapes the seminal relationship between pathogen growth rate and virulence

Abstract: A cornerstone of classical virulence evolution theories is the assumption that pathogen growth rate is positively correlated with virulence, the amount of damage pathogens inflict on their hosts. Such theories are key for incorporating evolutionary principles into sustainable disease management strategies. Yet, empirical evidence raises doubts over this central assumption underpinning classical theories, thus undermining their generality and predictive power. In this paper, we identify a key component missing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…However, an experimental evolution study that attempted similar selection failed to produce a response in M. bicuspidata (37). Alternatively, if slower parasite growth reduces parasite virulence and hence host mortality (consistent with the idea that higher virulence is associated with less prudent resource use (38)), there could be selection for slower growth of M. bicuspidata in response to O. pajunii. Unfortunately, experimental tests of this in this system seem unlikely to be successful, as multiple attempts to select M. bicuspidata for a variety of conditions have failed (37,39,40).…”
Section: Discussionmentioning
confidence: 94%
“…However, an experimental evolution study that attempted similar selection failed to produce a response in M. bicuspidata (37). Alternatively, if slower parasite growth reduces parasite virulence and hence host mortality (consistent with the idea that higher virulence is associated with less prudent resource use (38)), there could be selection for slower growth of M. bicuspidata in response to O. pajunii. Unfortunately, experimental tests of this in this system seem unlikely to be successful, as multiple attempts to select M. bicuspidata for a variety of conditions have failed (37,39,40).…”
Section: Discussionmentioning
confidence: 94%
“…A large body of theoretical literature examines the proposition that the evolution of virulence is driven by trade‐offs between transmission and mortality impacts on hosts, and by the likelihood of co‐occurrence within individual hosts of competing parasite strains (Cressler et al, 2016 ). Recent work has demonstrated that resource availability can modulate how this evolutionary process plays out (Lindsay et al, 2023 ). It goes beyond the scope of this paper to explore the many ways that might happen, but we do note that if reduced resources reduce host population size, one might expect an evolutionary reduction in virulence.…”
Section: Taking Stock: Summary and Opportunities For Future Workmentioning
confidence: 99%
“…For instance, harsh environmental conditions are expected to favor group living if it increases protection from extreme temperatures, improves foraging efficiency and enhances defense against predators (Krause and Ruxton 2002). Conversely, several parameters are expected to inhibit the evolution of group living, such as its inherently higher risk of visibility to predators (Lindström 1989), reduced per capita access to resources (e.g., food, nesting material, mating partners), higher levels of inter-individual competition, expression of aggressive behavior and sexual harassment (Mosser and Packer 2009;Elwood and Stolzenberg 2020), and increased risk of encountering and transmitting parasites and pathogens (Deere et al 2021;Lucatelli et al 2021;Ritchie et al 2021;Lindsay et al 2023).…”
Section: Introductionmentioning
confidence: 99%